2020
DOI: 10.1167/iovs.61.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Yes-Associated Protein 1 Promotes Astrocyte Proliferation and Maturation via Cytoplasmic Leukemia Inhibitory Factor Secretion in Oxygen-Induced Retinopathy

Abstract: PURPOSE. Purpose The role of endothelial Yes-associated protein 1 (YAP) in the pathogenesis of retinal angiogenesis and the astrocyte network in the mouse oxygen-induced retinopathy (OIR) model is unknown. METHODS. For in vivo studies, OIR was induced in conditional endothelial YAP knockout mice and their wild-type littermates. Retinal vascularization and the astrocyte network were evaluated by whole-mount fluorescence and Western blotting. In vitro experiments were performed in astrocytes cultured with human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…According to the previously published method [ 21 ], rats were anesthesized, 0.9% NaCl (4℃) was used to drain the blood from the heart, then, 4% polyformaldehyde was used to fix the tissue. The eyeball was quickly removed, soaked in 4% polyformaldehyde, and fixed on ice for 2 h. The eyeball was transferred to precooled PBS, and the retina was carefully separated.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previously published method [ 21 ], rats were anesthesized, 0.9% NaCl (4℃) was used to drain the blood from the heart, then, 4% polyformaldehyde was used to fix the tissue. The eyeball was quickly removed, soaked in 4% polyformaldehyde, and fixed on ice for 2 h. The eyeball was transferred to precooled PBS, and the retina was carefully separated.…”
Section: Methodsmentioning
confidence: 99%
“…YAP was shown to be a critical regulator of angiogenic sprouting in mouse retinal vessels in a manner dependent on VE-cadherin and Ang-2, probably as a transcriptional target of YAP, and it has been suggested that disruption of VE-cadherin in ECs would activate YAP nuclear translocation and transcriptional activity [ 109 ]. In fact, the sustained binding of YAP/TAZ to the transcription factor signal transducer and activator of transcription 3 (STAT3) was shown to promote angiogenesis in a manner dependent on the increase in Ang-2 expression in ECs [ 110 , 111 ]. Moreover, the endothelial YAP deletion reduced the LIF secretion, caused a disruption of the astrocytic network, and reduced the astrocyte differentiation.…”
Section: Feedback Between Astrocytes and Blood Vesselsmentioning
confidence: 99%
“…Moreover, the endothelial YAP deletion reduced the LIF secretion, caused a disruption of the astrocytic network, and reduced the astrocyte differentiation. In addition, in astrocyte cultures treated with conditioned medium from ECs that overexpressed YAP, increased astrocyte differentiation was observed [ 111 ]. This finding suggests that YAP regulates the LIF secretion from ECs that promote the maturation of astrocytic networks.…”
Section: Feedback Between Astrocytes and Blood Vesselsmentioning
confidence: 99%
“…In addition, recent findings on Yap haploinsufficiency indicate Müller glia dysfunction, late-onset cone degeneration, and reduced cone-mediated visual response [ 57 ]. Finally, YAP deficient endothelial cells show damaged retinal vascularisation and obstructive astrocyte network formation and maturation [ 58 ].…”
Section: Yap and Actin Cytoskeleton In Eye Development And Diseasementioning
confidence: 99%